1996
DOI: 10.1161/01.str.27.9.1629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BQ-123 and Tissue Plasminogen Activator on Vasospasm After Subarachnoid Hemorrhage in Monkeys

Abstract: Intracisternal TPA was efficacious against vasospasm in monkeys. Combination therapy with TPA and BQ-123 was not associated with reduction in efficacy of either drug or with evidence of toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…An additional 64 studies were excluded after reading the full text because they did not completely fulfill the inclusion criteria or they reported preliminary or incomplete data. Data from 70 papers were then extracted (Bilginer et al, 2009;Bulsara et al, 2006;Caner et al, 1996;Chang et al, 2010;Chen et al, 2009;Cheng et al, 2009;Chung and Lee, 1993;Cosentino et al, 1993;Espinosa et al, 1984;Findlay et al, 1988Findlay et al, , 1989Findlay et al, , 1990Grasso et al, 2002;Gul et al, 2010;Hanggi et al, 2009;Hariton et al, 1993;Hino et al, 1995;Itoh et al, 1993Itoh et al, , 1994Josko et al, 2000;Kanamaru et al, 1990Kanamaru et al, , 1991Kawada et al, 1999;Kawashima et al, 2000;Kim et al, 1996Kim et al, , 2000Kita et al, 1998;Kwan et al, 1997Kwan et al, , 2001Kwan et al, , 2006Laslo et al, 2006;Lewis et al, 1988;Lin et al, 2007;Macdonald et al, 1998aMacdonald et al, , b, 2004Marbacher et al, 2008;Matsui and Asano, 1994;Matsumura et al, 1991;McGirt et al, 2002McGirt et al, , 2006…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional 64 studies were excluded after reading the full text because they did not completely fulfill the inclusion criteria or they reported preliminary or incomplete data. Data from 70 papers were then extracted (Bilginer et al, 2009;Bulsara et al, 2006;Caner et al, 1996;Chang et al, 2010;Chen et al, 2009;Cheng et al, 2009;Chung and Lee, 1993;Cosentino et al, 1993;Espinosa et al, 1984;Findlay et al, 1988Findlay et al, , 1989Findlay et al, , 1990Grasso et al, 2002;Gul et al, 2010;Hanggi et al, 2009;Hariton et al, 1993;Hino et al, 1995;Itoh et al, 1993Itoh et al, , 1994Josko et al, 2000;Kanamaru et al, 1990Kanamaru et al, , 1991Kawada et al, 1999;Kawashima et al, 2000;Kim et al, 1996Kim et al, , 2000Kita et al, 1998;Kwan et al, 1997Kwan et al, , 2001Kwan et al, , 2006Laslo et al, 2006;Lewis et al, 1988;Lin et al, 2007;Macdonald et al, 1998aMacdonald et al, , b, 2004Marbacher et al, 2008;Matsui and Asano, 1994;Matsumura et al, 1991;McGirt et al, 2002McGirt et al, , 2006…”
Section: Resultsmentioning
confidence: 99%
“…Investigators used monkeys (Macaca species), dogs (mongrel or beagles), rabbits (Japanese or New Zealand species), rats (Sprague Dawley or Wistar species) and mice ( Espinosa et al (1984); Findlay et al (1988Findlay et al ( , 1989Findlay et al ( , 1990; Hariton et al (1993); Hino et al (1995); Kanamaru et al (1990Kanamaru et al ( , 1991; Kim et al (1996); Lewis et al (1988); Macdonald et al (2004); Nosko et al (1985); Steinke et al (1989); Suzuki et al (1998Suzuki et al ( , 1999 Wanebo et al (1997Wanebo et al ( , 1998; Zuccarello et al (1989Zuccarello et al ( , 1996Zuccarello et al ( , 1998 Method of induction of SAH Clot placement 17 (23) Espinosa et al (1984); Findlay et al (1988Findlay et al ( , 1989Findlay et al ( , 1990; Hariton et al (1993); Hino et al (1995); Kanamaru et al (1990Kanamaru et al ( , 1991Kanamaru et al ( , 2000; Kim et al (1996); Lewis et al ( Kanamaru et al (1990Kanamaru et al ( , 1991; Kawada et al (1999); Kawashima et al (2000); Kim et al (1996Kim et al ( , 2000; Kita et al (1998); Kwan et al (1997Kwan et al ( , 2001Kwan et al ( , 2006 Wanebo et al (1997<...>…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Raised ET levels have been reported in both the plasma and cerebrospinal fluid of patients after SAH, 11,12,23 in the plasma of patients after ischemic stroke, 10 and in experimental models of these conditions. 24 ET receptor antagonists prevent 13,25,26 and reverse 14,27 cerebral vasospasm in animal models of SAH.…”
Section: Discussionmentioning
confidence: 98%
“…This discrepancy is all the more difficult to understand since it has been reported that ET antagonists inhibit vasospasm in primates (147,148) as well as in other species. By far the most significant increases of ET concern ET-1, only sporadic amounts of ET-3 being noted in one report (141).…”
Section: Presence Of Ets In Csf After Sahmentioning
confidence: 96%